Broad temperature plateau for high ZTs in heavily doped p-type SnSe single crystals. Issue 2 (23rd December 2015) - Peng, Kunling; Lu, Xu; Zhan, Heng; Hui, Si; Tang, Xiaodan; Wang, Guiwen; Dai, Jiyan; Uher, Ctirad; Wang, Guoyu; Zhou, Xiaoyuan
Abstract : The increased number of carrier pockets near the Fermi level and the optimized carrier concentration in doped SnSe single crystal can lead to a high average ZT ave ∼ 1.2 from 300 K to 800 K and a peak ZT max value in excess of 2.0 at 800 K along the crystallographic b -axis. Abstract : Excellent thermoelectric performance is obtained over a broad temperature range from 300 K to 800 K by doping single crystals of SnSe. The average value of the figure of merit ZT, of more than 1.17, is measured from 300 K to 800 K along the crystallographic b -axis of 3 at% Na-doped SnSe, with the maximum ZT reaching a value of 2 at 800 K. The room temperature value of the power factor for the same sample and in the same direction is 2.8 mW mK −2, which is an order of magnitude higher than that of the undoped crystal. Calculations show that Na doping lowers the Fermi level and increases the number of carrier pockets in SnSe, leading to a collaborative optimization of the Seebeck coefficient and the electrical conductivity. The resultant optimized carrier concentration and the increased number of carrier pockets near the Fermi level in Na-doped samples are believed to be the key factors behind the spectacular enhancement of the average ZT .